Evaluation of Online Consumer Health Information for Idiopathic Scoliosis Identified by a Google Search - Heady, Sarah C.; Weaver, Marissa A.; Berg, Gina M.; Manlove, Emily M.; Thuener, Jennifer E.; Burton, Douglas C. (Kansas Journal of Medicine, 2018)
Introduction. This study sought to assess the quality of online consumer health information about idiopathic scoliosis. Previous studies showed that quality of online health information varies and often lacks adherence to expert recommendations and guidelines. Nevertheless, 72% of internet users seek health information online. A 2005 analysis of online scoliosis information found that the information was limited and of poor quality. Methods. Two reviewers vetted the top 10 websites resulting from a GoogleTM search for “scoliosis.” Content was organized into categories and rated by three physician evaluators using a 1 - 5 scale based on quality, accuracy, completeness of information, readability, and willingness to recommend. Additional information, such as number of ads and Flesch-Kinkaid reading level, also was collected. Results. The average overall physician score was 47.6 (75 possible). All websites included content that was mostly accurate but varied in completeness. Physicians unanimously recommended Mayo Clinic, MedicineNet, and Kids Health; none recommended the GoogleTM Knowledge Graph. The Scoliosis Research Society website reached the highest overall physician score. Readability ranged from 7th grade to college level; only that of Kids Health was below 10th grade level. Conclusions. Most essential information provided by the websites was accurate and generally well rated by physicians. Website ranking by physicians was inconsistent with the ranking order by GoogleTM, indicating that health seekers reviewing the top GoogleTM-ranked websites may not be viewing the websites rated highest by physicians. Physicians should consider patient literacy in website recommendations, as many have an above average literacy level. Kans J Med 2018;11(4):95-101.